Research on the Letter to the Galatians: 2000-2010 - D. F. Tolmie (Acta Theologica)
This article is devoted to an overview of research published on the Letter to the Galatians from 2000 to 2010. An attempt is made to paint as detailed a picture as possible of the research on the letter, but in such a way that the gist of the contributions that have been selected is also communicated, albeit very briefly. Research on Galatians in the following five areas is discussed: introductory issues (e.g., authorship, opponents and recipients), the Wirkungsgeschichte of the letter, interpretative approaches to the letter, studies of particular verses/passages in the letter and the theology of the letter.